LncRNA Landscape of Coronary Atherosclerosis Reveals Differentially Expressed LncRNAs in Proliferation and Migration of Coronary Artery Smooth Muscle Cells - Zhou, Yaqing; Zhang, Sheng; Ji, Wenfeng; Gan, Xiongkang; Hua, Lei; Hou, Can; Chen, Jiaxin; Wang, Yanjun; He, Shu; Zhou, Hanxiao; Jia, Enzhi (Frontiers in Cell and Developmental Biology, 2021)
We aimed to investigate differentially expressed long noncoding RNAs (lncRNAs) and messenger RNAs (mRNAs) in atherosclerosis and validate the expression of lncRNAs and coexpressed target genes in proliferation and migration models of human coronary artery smooth muscle cells (HCASMCs). Ten coronary artery specimens from a subject who died from a heart attack were employed. The pathological analysis was analysed by haematoxylin and eosin (H&E) staining, and the lncRNAs and mRNAs were identified by RNA sequencing. Bioinformatic analyses were performed to predict possible mechanisms. The proliferation and migration of HCASMCs were induced with ox-LDL. Differentially expressed lncRNAs and mRNAs were validated by quantitative real-time polymerase chain reaction (qRT-PCR). In this study, 68 lncRNAs and 222 mRNAs were identified differentially expressed in atherosclerosis. GO and KEGG enrichment analyses showed that the Fanconi anemia pathway may be involved in atherosclerosis. GON4L was found to be the colocalized target gene of LNC_000439, and 14 genes had high correlations with the expression of 7 lncRNAs. In addition, 9 lncRNA-miRNA-mRNA networks were constructed, and 53 coexpressed gene modules were detected with WGCNA. LNC_000684, LNC_001046, LNC_001333, LNC_001538 and LNC_002115 were downregulated, while LNC_002936 was upregulated in proliferation and migration models of HCASMCs. Totally, 6 coexpressed mRNAs were upregulaed in HCASMCs. This study suggests that the differentially expressed lncRNAs identified by RNA-seq and validated in smooth muscle cells may be a target for regulating HCASMC proliferation and migration in atherosclerosis, which will provide a new diagnostic basis and therapeutic target for the treatment of cardiovascular diseases.